2022
DOI: 10.3390/ma15134677
|View full text |Cite
|
Sign up to set email alerts
|

Experimental and Numerical Investigation of Intact, Defective and Repaired Countersunk Composite Joints under Tensile Loading

Abstract: Bolted joints are commonly used for assembling carbon fiber/resin composite structures. Since drilling may generate defects at hole edges which affect mechanical properties, it is of great engineering significance to develop proper repair methods to restore the mechanical properties of the defective parts. However, there are few studies on hole edge defects and their repair methods. Therefore, a novelty short fiber filling repair method was proposed to repair defective holes in this study. The mechanical prope… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 25 publications
0
1
0
Order By: Relevance
“…At the same time, Lu-ana Pereira Dalla Mariga et al investigated the impact of geometrical tolerance on single-lap composite joints riveted with two fasteners [ 30 , 31 ]. Countersunk bolts have been investigated for the correction of drilling-induced faults, as well as the influence of stacking sequences on the bearing strength of composite bolted joints [ 32 , 33 , 34 ]. Manasi Palwankar et al demonstrated a revised fixture for bolted composite joint testing that can support countersunk fasteners [ 35 ].…”
Section: Introductionmentioning
confidence: 99%
“…At the same time, Lu-ana Pereira Dalla Mariga et al investigated the impact of geometrical tolerance on single-lap composite joints riveted with two fasteners [ 30 , 31 ]. Countersunk bolts have been investigated for the correction of drilling-induced faults, as well as the influence of stacking sequences on the bearing strength of composite bolted joints [ 32 , 33 , 34 ]. Manasi Palwankar et al demonstrated a revised fixture for bolted composite joint testing that can support countersunk fasteners [ 35 ].…”
Section: Introductionmentioning
confidence: 99%